Mindful Self-Compassion to Improve Students' Quality of Life - Gian Sugiana Sugara; Puteri Karenina; Dewang Sulistiana (Edupotensia, 2025)
This study investigated the impact of classical guidance based on a mindful self-compassion program on improving adolescents’ quality of life. Employing a one-group pretest-posttest experimental design, the intervention was delivered over a six-week period, with each session lasting approximately 45 to 60 minutes. Participants completed the Adolescent Quality of Life Inventory (AQoLI) prior to and following the intervention. A total of 21 participants took part in both the pre- and post-intervention assessments. The findings revealed a significant improvement in overall quality of life, with a large effect size observed (d = 0.62). Additionally, notable improvements were identified in specific domains, including self-functioning (d = 0.49), social functioning (d = 0.47), and personal growth (d = 0.67). These results support the initial hypothesis that participants would experience enhanced quality of life following the intervention. While these findings are promising, the study's limitations should be noted. The small sample size and absence of a control group constrain the generalizability of the results. Further research employing randomized controlled trial designs and follow-up assessments is warranted to confirm the efficacy of mindful self-compassion programs in promoting adolescents’ quality of life